ANALISIS PENYELESAIAN WANPRESTASI KONTRAK KERJA KONSTRUKSI DITINJAU DARI ASAS KESEIMBANGAN - Lubna Tabriz Sulthanah (Fakultas Hukum Universitas Udayana, 2021)
The purpose of this study is to answer how the principle of balance can affect the fulfillment of performance in construction work contracts and how to analyze the legal settlement of defaults based on Decision Number 27/Pdt.G/2018/PN.Bdg. The method used in this research is normative juridical through a statutory approach and a case approach using secondary data. This study concludes, first, that the principle of balance in a construction work contract affects achievement because service providers who apply the principle of balance and service users who can choose a service provider carefully will achieve success in construction work. Second, based on the judge's consideration accompanied by strong evidence, the service provider as the defendant was proven to have defaulted because he was late in completing the construction work of the Seres Springs Hotel & Spa construction project. The defendant was sentenced to pay compensation costs in lieu of costs incurred by the plaintiff because of the actual losses suffered and the losses that should have been obtained.